Reproductive phasiRNAs regulate reprogramming of gene expression and meiotic progression in rice - Zhang, Yu-Chan; Lei, Meng-Qi; Zhou, Yan-Fei; Yang, Yu-Wei; Lian, Jian-Ping; Yu, Yang; Feng, Yan-Zhao; Zhou, Ke-Ren; He, Rui-Rui; He, Huang; Zhang, Zhi; Yang, Jian-Hua; et al. (Nature communications, 2020)
Plant spermatogenesis is a complex process that directly affects crop breeding. A rapid change in gene abundance occurs at early meiosis prophase, when gene regulation is selective. However, how these genes are regulated remains unknown. Here, we show that rice reproductive phasiRNAs are essential for the elimination of a specific set of RNAs during meiotic prophase I. These phasiRNAs cleave target mRNAs in a regulatory manner such that one phasiRNA can target more than one gene, and/or a single gene can be targeted by more than one phasiRNA to efficiently silence target genes. Our investigation of phasiRNA-knockdown and PHAS -edited transgenic plants demonstrates that phasiRNAs and their nucleotide variations are required for meiosis progression and fertility. This study highlights the importance of reproductive phasiRNAs for the reprogramming of gene expression during meiotic progression and establishes a basis for future studies on the roles of phasiRNAs with a goal of crop improvement. 21-nucleotide phased secondary siRNAs are expressed in the developing rice anthers during meiosis. Here, the authors show that phasiRNAs can cleave target mRNA and act to ensure the progression of meiosis and fertility in rice.